miR-134: A Human Cancer Suppressor? - Jing-Yu Pan; Feng Zhang; Cheng-Cao Sun; Shu-Jun Li; Guang Li; Feng-Yun Gong; Tao Bo; Jing He; Rui-Xi Hua; Wei-Dong Hu; Zhan-Peng Yuan; Xin Wang; et al. (Molecular Therapy: Nucleic Acids, 2017)
MicroRNAs (miRNAs) are small noncoding RNAs approximately 20–25 nt in length, which play crucial roles through directly binding to corresponding 3′ UTR of targeted mRNAs. It has been reported that miRNAs are involved in numerous of diseases, including cancers. Recently, miR-134 has been identified to dysregulate in handles of human cancers, such as lung cancer, glioma, breast cancer, colorectal cancer, and so on. Increasing evidence indicates that miR-134 is essential for human carcinoma and participates in tumor cell proliferation, apoptosis, invasion and metastasis, drug resistance, as well as cancer diagnosis, treatment, and prognosis. Nevertheless, its roles in human cancer are still ambiguous, and its mechanisms are sophisticated as well, referring to a variety of targets and signal pathways, such as STAT5B, KRAS, MAPK/ERK signal pathway, Notch pathway, etc. Herein, we review the crucial roles of miR-134 in scores of human cancers via analyzing latest investigations, which might provide evidence for cancer diagnose, treatment, prognosis, or further investigations. Keywords: miR-134, human cancer, microRNA